Kajian Representasi Budaya Pendidikan Dalam Film Laskar Pelangi - Santi Manda Sari; Abdullah Hasibuan (Jurnal Akuntansi, Manajemen dan Ekonomi Digital, 2022)
Film is no longer defined as a work of art but rather as a social practice and mass communication. In the perspective of social practice, film involves a complex and dynamic interaction of the supporting elements of the production, distribution and exhibition processes. While the film in the perspective of mass communication is interpreted as a representation of the message conveyed to the audience. Representation as a large part of cultural studies is centered on the question of how the world is socially constructed and described from us and by us interpreted in films as an intergenerational cultural heritage. So the film as a medium of mass communication also functions as a cultural transmission in society. Laskar Pelangi film with the theme of education and social is understood as a representation of cultural reality that shows how a culture works and lives in a society. So that the film can be said as an effective medium in cultural learning by the community. This research is a cultural studies research with a qualitative research approach. Through the unit of analysis in the form of Laskar Pelangi film, Barthes' Semiotics analysis is used which can cover the signifier, the signified, the denotative meaning and the existing connotative meaning. Thus, a number of myths and ideologies were found hidden behind the cultural representations shown in the film. The results of this research are a number of concepts related to cultural studies. Such as the concept of marginalization of society, the hegemony of power, the concept of identity. the concept of gender, modernization, ethnography related to the basic framework of anthropology, and cultural materialism. The whole concept reflects a number of findings of educational culture such as the still weak education sector due to the distribution of the education budget that has not been maximized, the pretension of education because it is more concerned with prestige than skills, lack of appreciation for the process, education is still measured from mere statistics, and the commercialization of education.Keywords: Representation, culture, education, film